Educational Broadcasting in Nigeria: Trends, Challenges, and Opportunities - Sanusi, Bernice O.; Abdulkareem , Lukman; Lawal , Olusola Ayinde (Corpus Intellectual, 2025)
This study examined educational broadcasting in Nigeria, with a focus on emerging trends, prevailing challenges, and potential opportunities. With inadequate infrastructure and limited access to quality education, educational broadcasting has proven to be a vital tool for enhancing learning experiences and extending educational access to diverse populations. Technology integration has facilitated the development of interactive and engaging content designed to cater to various learning needs. Notably, the adoption of remote learning during the outbreak of the COVID-19 pandemic underscored the importance of broadcast media in learning. Utilizing a conceptual research method, the study identifies key trends, including the digital transformation of the educational landscape and the increasing focus on interactive and participatory learning models. However, there are challenges in funding, sustainability, technological infrastructure, and audience engagement. The study concludes that educational broadcasting in Nigeria holds promising prospects for transformative growth through the adoption of emerging technologies and inclusive educational practices. It recommends increased investment in infrastructure and the development of sustainable models to ensure equitable access to quality educational resources across the nation.